Dinitrosyl iron complexes (DNICs) as inhibitors of the SARS-CoV-2 main protease. Issue 67 (2nd August 2021) - Pectol, D. Chase; DeLaney, Christopher R.; Zhu, Jiyun; Mellott, Drake M.; Katzfuss, Ardala; Taylor, Zane W.; Meek, Thomas D.; Darensbourg, Marcetta Y.
Abstract : By repurposing DNICs designed for other medicinal purposes, the possibility of protease inhibition was investigated in silico using AutoDock 4.2.6 (AD4) and in vitro via a FRET protease assay. Abstract : By repurposing DNICs designed for other medicinal purposes, the possibility of protease inhibition was investigated in silico using AutoDock 4.2.6 (AD4) and in vitro via a FRET protease assay. AD4 was validated as a predictive computational tool for coordinatively unsaturated DNIC binding using the only known crystal structure of a protein-bound DNIC, PDB–; 1ZGN (calculation RMSD = 1.77). From the in silico data the dimeric DNICs TGTA–RRE, [(μ-S-TGTA)Fe(NO)2 ]2 (TGTA = 1-thio- β -d -glucose tetraacetate) and TG–RRE, [(μ-S-TG)Fe(NO)2 ]2 (TG = 1-thio- β -d -glucose) were identified as promising leads for inhibition via coordinative inhibition at Cys-145 of the SARS-CoV-2 Main Protease (SC2M pro ). In vitro studies indicate inhibition of protease activity upon DNIC treatment, with an IC50 of 38 ± 2 μM for TGTA–RRE and 33 ± 2 μM for TG–RRE. This study presents a simple computational method for predicting DNIC–protein interactions; the in vitro study is consistent with in silico leads.